Meta-Analysis the Effects of Hypertension, High Density Lipoprotein, and Diabetes Mellitus on the Risk of Stroke - Najlah Amalia; Vitri Widyaningsih; Burhannudin Ichsan (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Stroke is defined as an interruption of the blood supply to the brain which is usually caused by a blockage by a blood clot. This causes disruption of the supply of oxygen and nutrients to the brain resulting in damage to brain tissue. This study aims to analyze and estimate the effect of hypertension, high-density lipoprotein, and diabetes mellitus on the risk of stroke. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: adults. Intervention: hypertension, high-density lipoprotein, and diabetes mellitus. Comparison: normal blood pressure, normal HDL, and normal blood sugar. Outcome: strokes. The databases used were PubMed, Google Scholar, Science Direct, and Proquest with keywords (hypertension OR